Pendidikan Karakter Berbasis Kebudayaan Sekolah di Sekolah Dasar (Sebuah Kajian Literatur) - Suhartono, Suhartono; Mawarti, Nana Suko; Mawardi, Arif; Sukadi, Sukadi; Sujanto, Sujanto; Pebriyanto, Helmi (ANWARUL, 2022)
School culture-based character education is a character education approach that makes school culture the main guideline for developing values. Writing this article aims to describe the pattern of school culture-based character education carried out at the elementary school level. This research was conducted using a qualitative descriptive method with a literature study approach. Sources of data in this study are in the form of articles, theses, books, and also scientific papers which are analyzed based on existing problems. The research data is in the form of sentence excerpts that represent the focus of the research. The data is collected through note-reading techniques. Once collected, the data were analyzed qualitatively using interactive techniques. The results of the study show that school culture-based character education at the elementary school level is very diverse. This diversity arises because of adjustments between one school institution and another school institution. This also shows that school culture-based character education is a non-rigid approach so that it can be an alternative that is quite effective in shaping the character of students.